The ubiquitin‐proteasome system in positive‐strand RNA virus infection. (11th July 2012) - Choi, Alex GoEun; Wong, Jerry; Marchant, David; Luo, Honglin
SUMMARY Positive‐stranded RNA viruses, like many other viruses, have evolved to exploit the host cellular machinery to their own advantage. In eukaryotic cells, the ubiquitin‐proteasome system (UPS) that serves as the major intracellular pathway for protein degradation and modification plays a crucial role in the regulation of many fundamental cellular functions. A growing amount of evidence has suggested that the UPS can be utilized by positive‐sense RNA viruses. The UPS eliminates excess viral proteins that prevent viral replication and modulates the function of viral proteins through post‐translational modification mediated by ubiquitin or ubiquitin‐like proteins. This review will discuss the current understanding of how positive RNA viruses have evolved various mechanisms to usurp the host UPS to modulate the function and stability of viral proteins. In addition to the pro‐viral function, UPS‐mediated viral protein degradation may also constitute a host defense process against some positive‐stranded RNA viral infections. This issue will also be discussed in the current review. Copyright © 2012 John Wiley & Sons, Ltd.